The place of red meat consumption in nutrition habits and factors affecting red meat consumption - Kızılaslan, Nildem (Progress in Nutrition, 2022)
In addition to being the most important source of animal protein, red meat is important for human nutrition and health with vitamins, minerals antioxidant substances, and various nutritious elements it contains. In the study, it was aimed to determine individuals’ red meat consumption habits, purchasing behaviors, and factors affecting consumer decisions. In line with this purpose, a questionnaire was administered to 410 consumers chosen through proportional sampling method with 95% confidence interval and 5% error margin. In measuring the factors that individuals consider regarding the place they purchase red meat according to their income levels, a 5-Point Likert type scale, the lowest score being 1 and the highest score being 5, was used. In addition, individuals’ Body Mass Indexes (BMIs) were calculated. The average income level of the individuals was 4,158.21 TL per month, and their average monthly expenditure on food was found as 978.57 TL. The female individuals’ mean BMI was determined to be 24.43±4.05, while it was found to be 26.78±4.19 for male individuals. The average red meat consumption of the participants was found to be 85.85%. It was observed that the income level of the individuals was a factor affecting their amount of red meat consumption. As the level of income increased, so did red meat consumption. In the study, it was determined that the individuals consumed an average of 3,46±1,86 kg red meat a month. According to analysis results, it was determined that there was a statistically significant relationship between red meat consumption and the individuals’ income levels, food expenditures, and their professions. No statistically significant relationship was found between red meat consumption and the individuals’ age, education, gender, marital status, and BMI (kg/m2) of the male and female individuals. In conclusion, it can be claimed that consumption of red meat that is of high quality and contains protein in line with the consumers’ preferences in recommended amounts in daily diet will benefit individuals in terms of health. In this context, red meat consumption should be encouraged in a balanced way in line with consumption texture, and necessary measures that will ensure its consumption as an important element of balanced nutrition should be taken.